2003
DOI: 10.1002/cyto.a.10054
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is generated via the mitochondrial respiratory chain during plant cell apoptosis

Abstract: Background: We present evidence that in plant cells DNA damage induced by the topoisomerase trapping drug camptothecin induces oxidative stress via the mitochondrial respiratory chain. Methods: Flow cytometry was used to analyse mitochondrial respiratory chain activity by simultaneous measurement of mitochondrial generation of reactive oxygen intermediates (ROI) and mitochondrial membrane potential (⌬⌿ m ), in live functioning sugarbeet protoplasts. The mitochondrial respiratory chain function was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Many strategies aimed at slowing down the aging process or preventing cancer are based on protection of DNA from oxidative damage, primarily by scavenging the endogenous oxidants. While approaches to measure the presence of oxidants within the cell have been developed, 10,11 the possibilities for detecting DSBs generated by endogenous oxidants are limited. DNA damage assessment by the comet methodology 12 is rather cumbersome, lacks the desired sensitivity and cannot provide information on the relationship between DNA damage and the cell cycle phase in which the damage occurred.…”
mentioning
confidence: 99%
“…Many strategies aimed at slowing down the aging process or preventing cancer are based on protection of DNA from oxidative damage, primarily by scavenging the endogenous oxidants. While approaches to measure the presence of oxidants within the cell have been developed, 10,11 the possibilities for detecting DSBs generated by endogenous oxidants are limited. DNA damage assessment by the comet methodology 12 is rather cumbersome, lacks the desired sensitivity and cannot provide information on the relationship between DNA damage and the cell cycle phase in which the damage occurred.…”
mentioning
confidence: 99%
“…Inhibition of complex IV should not promote superoxide generation by Q o because the back-up of the high potential chain should inhibit QH 2 oxidation (Crofts 2004). That a threshold level of mitochondrial generated ROS may be important for cell death induction is broadly consistent with studies that have shown a very early and localized increase in mitochondrial ROS (Naton et al 1996;Yao et al 2002;Weir et al 2003;Yao and Greenberg 2006). In some studies, this ROS burst was shown to coincide with (and was likely the result of) a hyperpolarization of the inner mitochondrial membrane (Naton et al 1996;Weir et al 2003).…”
Section: A Specific Restriction Of Electron Flow At Complex III Can Amentioning
confidence: 59%
“…One possible explanation for this observation could be formation of intracellular coordination complex of malic acid with nickel ions (46, 49 -53), which reduces free ion activity and thereby modulates ROS. In a previous study, malic acid reduced ROS in the early steps of apoptosis induction in protoplasts (19).…”
Section: Discussionmentioning
confidence: 74%